KNOWLEDGE AND AWARENESS OF NYCTOPHOBIA AMONG DENTAL STUDENTS - A QUESTIONNAIRE SURVEY - Sheron Blessy, Dhanraj Ganapathy, L. Keerthi Sasanka, (Drugs and Cell Therapies in Hematology, 2022)
Introduction: Nyctophobia is fear of darkness , which increases the anxiety level because of darkness and initiates the fear of it. Aim: The aim of the study is to evaluate Nyctophobia among the dental students. Materials and Methods: The study was conducted among 103 students from Saveetha Dental College and Hospitals, Chennai . Simple random sampling was done here. (SPSS) software version 23.0 and Pearson’s chi-square association was used to evaluate the fear of nyctophobia among the dental students. Results: About 43.14% are known to have the fear of darkness where 30.39% were females and 12.75% of male and about 56.86% do not have the fear of darkness where 28.43% were females and males . About 52.94% dramatized situations involving darkness, sometimes about 28.43% were female and 24.51% were male . About 7.84% dramatized all the time where 4.90% were female and 2.94% were male. About 3.92% have not taken any medication to cope up where 2.94% were female 0.98% were male. About 96.08% had not taken any medication where 55.88% were female and 40.20% were male. Conclusion: It can be concluded that the fear of darkness has been a major problem. So more awareness is needed to overcome nyctophobia by taking some measures to cope up the fear of darkness.